An Evidence-Based Planned Transformative Technologies and Curriculum Development In Business And Entrepreneurship Education In A Growing University - Stella Chinye Chiemeke; Felicia Ofuma Mormah (Research Trend in Technology and Management, 2026)
The rapid evolution of technology has significantly influenced educational practices, especially in business and entrepreneurship disciplines. The integration of evidence-based transformative technologies into business and entrepreneurship education is essential for nurturing competent graduates who can thrive in ever-evolving markets. As universities grow, they must prioritize innovative curriculum development that aligns with industry standards and effectively prepares students for future challenges. This article discusses the incorporation of evidence-based transformative technologies into curriculum development and highlights strategies for fostering innovative learning environments in a growing university setting. It emphasizes the importance of aligning educational curricula with industry demands and technological advancements to prepare students effectively for real-world challenges and opportunities. This document review research based paper